A Narrative Review: Phentermine and Topiramate for the Treatment of Pediatric Obesity - Kim A; Nguyen J; Babaei M; Kim A; Geller DH; Vidmar AP (Dove Medical Press, 2023)
Anthony Kim,1 Jennifer Nguyen,2 Mahsa Babaei,2 Ahlee Kim,1,2 David H Geller,1,2 Alaina P Vidmar1,2 1Department of Pediatrics, Keck School of Medicine, University of Southern California, Los Angeles, CA, USA; 2Children's Hospital Los Angeles and Keck School of Medicine of University of Southern California, Department of Pediatrics, Center for Endocrinology, Diabetes and Metabolism, Los Angeles, CA, USACorrespondence: Alaina P Vidmar, Diabetes & Obesity Program, Center for Endocrinology, Diabetes and Metabolism, Department of Pediatrics, 4650 Sunset Boulevard, Mailstop #61, Los Angeles, CA, 90027, USA, Tel +1 323 361-3385, Fax +1 323 361-1301, Email avidmar@chla.usc.eduAbstract: The prevalence of pediatric obesity has increased exponentially over the past four decades. The American Academy of Pediatrics recently released updated clinical practice guidelines highlighting the importance of identifying pediatric obesity as a chronic disease. The guidelines support consideration of concurrent treatment with intensive lifestyle interventions, obesity pharmacotherapy, and bariatric surgery. The dramatic rise in pediatric obesity has spurred interest in utilizing obesity pharmacotherapy to support sustained weight reduction in pediatric cohorts, in the hopes of preventing the emergence of later-appearing, significant co-morbidities. Despite the enormous demand, the obstacles posed by performance of needed clinical trials in the pediatric population markedly limits available pharmacotherapy for the treatment of obesity in pediatrics. Currently, there are five medications approved by the Food and Drug Administration for use in youth with obesity. In 2022, the phentermine/topiramate (PHEN/TPM), once-daily, controlled-release, combination product received FDA approval, for the indication of chronic weight management, in youth with obesity, ages 12 years and older. The objectives of this narrative review are to: (1) Review the mechanism of action of phentermine and topiramate, (2) Summarize the safety and efficacy data of topiramate and phentermine use as both monotherapies and in combination, and (3) Discuss clinical practice guidelines and clinical implications, for the use of these agents in youths with obesity.Keywords: phentermine, topiramate, pediatric obesity, obesity pharmacotherapy